Dual-chamber paced patients without high-degree AV block at baseline are at higher risk of atrial arrhythmias when inappropriately paced in the right ventricle: a sub-analysis of the EMERALD study. (3rd October 2022) - Di Cori, A; Lapuerta, J A; Dan, D; Hansen, J; Trim, G; Ayala-Paredes, F; Coutu, B; Martin-Asenjo, R; Contardi, D; Olivier, A; Clark, R; Bongiorni, M G
Abstract: Background/Introduction: Unnecessary right ventricular pacing (RVP) can have deleterious effects including an increased risk of atrial arrhythmia (AA) and heart failure during follow-up (FU) in dual-chamber (DR) paced patients. While previous studies have shown that these increased risks occur with RVP>40%, the EMERALD Study demonstrated an increased risk for RVP>1%. Few data exist on the interaction between the amount of RVP and the presence/absence of high-degree atrio-ventricular block (AVB) as a pacing indication at baseline. Purpose: The EMERALD (AssEssment of CoMorbiditiEs & Atrial ArRhythmiA Burden In DuaL-Chamber PaceD Patients) Study was a real-world registry designed to assess the impact of RVP burden on the risk of developing persistent/permanent AA (Pers-AA) over 2-year FU. The primary endpoint was the difference in Pers-AA in subjects with high (>40%) and low (<40%) RVP. This sub-analysis aimed to identify the interaction between RVP and the presence/absence of high-degree AVB at baseline in relation to the incidence of Pers-AA. Methods: EMERALD was a non-interventional, prospective, multi-center registry conducted at 186 centers in 12 countries. Enrolled subjects were implanted with a DR pacemaker according to ESC or ACC/AHA/HRS guidelines. Subjects were excluded if they had a history of Pers-AA. Devices could be implanted as de-novo, replacement or upgrade therapy. Programming was left to the investigators' discretion. Subjects were followed for at least 24 months. Pers-AA was defined as: >22 h/day of AA for >7 consecutive days; Pers-AA diagnosed during any FU visit; AA-related ablation or cardioversion carried out in the FU period. We compared the incidence of Pers-AA between subjects with (n=1529) and without (n=1948) high-degree AVB as a baseline pacing indication. Results: Eligible FU data were available for n=3477 subjects. The overall population was nearly evenly split - High RVP (47.7%) and Low RVP (52.3%). In the High RVP group, 11.7% experienced at least one Pers-AA episode versus 9.1% in the Low RVP group (p=0.006). In this sub-analysis, the prevalence of RVP>40% was higher in patients with high-degree AVB at baseline (74% vs 26%). Although the incidence of Pers-AA was similar in the group with high-degree AVB at baseline (High RVP 8.7% vs Low RVP 7.4%), in the group without high-degree AVB at baseline, those with High RVP developed a significantly higher incidence of Pers-AA (High RVP 18.2% vs Low RVP 9.5%, p value for interaction 0.0275; Figure 1). An analysis with a newly identified RVP threshold of 1% confirmed a high incidence of Pers-AA only in the group without high-degree AVB at baseline (18% vs 3.5%, p value for interaction 0.2265; Figure 2). Conclusions: The baseline pacing indication sub-analysis of the EMERALD Study shows that patients without high-degree AVB as a baseline indication are at highest risk of Pers-AA. Efforts should be made to avoid any unnecessary RVP in this subgroup of patients. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): MicroPort CRM (Clamart, France)